Preoperative paraspinous muscle sarcopenia and physical performance as prognostic indicators in non‐small‐cell lung cancer. Issue 3 (4th March 2021) - Tanaka, Shinya; Ozeki, Naoki; Mizuno, Yota; Nakajima, Hiroki; Hattori, Keiko; Inoue, Takayuki; Nagaya, Motoki; Fukui, Takayuki; Nakamura, Shota; Goto, Masaki; Sugiyama, Tomoshi; Nishida, Yoshihiro; et al.
Abstract: Background: Despite the associations of both preoperative sarcopenia and physical performance with post‐operative mortality in non‐small‐cell lung cancer (NSCLC), there have been no comprehensive studies of the impact of physical status on prognosis. This study was performed to investigate the prognostic significance of preoperative sarcopenia and physical performance in NSCLC. Methods: This retrospective cohort study was performed in NSCLS patients undergoing curative lung resection at a university hospital between January 2014 and December 2017. The patients were divided into four groups according to the skeletal muscle index [sarcopenia (lowest sex‐specific tertile) and non‐sarcopenia] and 6 min walking distance (6MWD) [short distance (<400 m) and long distance (≥400 m)]. Sarcopenia was assessed by preoperative cross‐sectional areas of right and left paraspinous muscles at the level of the 12th thoracic vertebra from computed tomography images, and physical performance was determined by preoperative 6MWD. The primary and secondary endpoints were post‐operative overall survival (OS) and disease‐free survival (DFS). Results: The 587 patients [mean age: 68.5 ± 8.8 years, 399 men (68%)] included in the study were divided into the non‐sarcopenia/long‐distance group (58%), sarcopenia/long‐distance group (26%), non‐sarcopenia/short‐distance group (9%), and sarcopenia/short‐distance group (7%). A total of 109 (18.6%) deaths and 209 (35.6%) combined endpoints were observed over a mean follow‐up of 3.1 ± 1.3 years. After adjusting for other covariates, the sarcopenia/short‐distance group showed significant associations with shorter OS (hazard ratio, 3.38; 95% confidence interval, 1.79–6.37; P  < 0.001) and DFS (hazard ratio, 2.11; 95% confidence, 1.27–3.51; P  = 0.004) compared with the non‐sarcopenia/long‐distance group on multivariate analyses. Although not significant, adding skeletal muscle index and 6MWD to the pre‐existing risk model increased the area under the curve on time‐dependent receiver operating characteristic curve analysis for OS and DFS, except within 2 years of surgery. Conclusions: The presence of both preoperative paraspinous muscle sarcopenia and short distance in 6MWD had an adverse effect on post‐operative prognosis in patients with NSCLC, suggesting that preoperative assessment of thoracic sarcopenia and physical performance may be useful for risk stratification of surgical candidates with potential for targeted interventions.